Advances in auditory implants. Issue 3 (June 2023) - Iwasaki, Satoshi
Abstract: Auditory implants are classified into bone conduction (BAHA and Bonebridge; BB) and active middle ear implants (Vibrant Soundbridge; VSB) that stimulate cochlear hair cells, and cochlear implants (CIs) that stimulate neural structures. CIs should be performed as early as possible, and bilateral CIs have become popular because sound localization and speech recognition can be improved. CI is also considered a desirable treatment option for patients with single-sided deafness. VSB provides a safe and effective option for patients with conductive or mixed hearing loss and moderate to severe sensorineural hearing loss (SNHL); however, it use in patients with conductive or mixed hearing loss have only been approved in Japan. BAHA and BB implants have been approved by national insurance in Japan as bone conduction implants for patients with conductive or mixed hearing loss. Two fully implantable devices (Cochlear Carina and Envoy Esteem) are provided for patients with SNHL.